Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Pulau Jawa 2016-2020 - Jihan Safitri (Jurnal Ilmu Ekonomi, 2022)
This study aims to study the impact of fiscal decentralization on regional economic growth in Java Island in 2016-2020. Tax reform, implemented since Law no. 28 of 2009 which has been able to encourage local authorities to improve justice between regions so that regional inequality does not occur. This study uses multiple regression analysis, namely panel data regression with 5 samples of provinces on the island of Java, the results show that the development of the ratio of regional independence, regional investment and regional expenditures increases. Then, for the comparison of the ratio of regional independence, regional investment and regional expenditures have a significant positive relationship with Java Island